Improving Arabic Listening Skills Through Audio Visual (Animated Video) for Students - Selfiani, Astria; Hasmawati, Hasmawati (Interference: Journal of Language, Literature, and Linguistics, 2025)
Abstract. This study aims to improve the Arabic listening skills of seventh-grade students at SMP IT Ar Rahmah Makassar through the use of audio visual (animated videos). This research is a classroom action research that consists of two cycles, with each cycle comprising the stages of planning, implementation, observation, and reflection. The subjects of the study are 32 seventh-grade students. The research data consists of qualitative and quantitative data. Qualitative data is obtained from the observation results of teachers and students. Quantitative data is obtained through Arabic listening skill tests at the end of cycles I and II. The average listening skill score obtained by students in cycle I was 71.25, and in cycle II, the average score was 91.87. The improvement in listening skills from cycle I to cycle II was 20.62. This indicates that the Arabic listening skills of seventh-grade students at SMP IT Ar Rahmah Makassar improved with the use of audio visual media (animated videos). Keywords: Listening Skills, Animated Videos, Arabic Language